Work flexibility and work-life balance: Exploring the moderating role of resilience in Generation Z and Millennial - Aniek Rumijati; Khusnul Rofida Novianti; Ratya Shafira Arifiani; Arif Budi Wurianto; Nur Fadhilah (Universitas Ahmad Dahlan, 2025)
Remote workers from Generation Z and Millennial increasingly seek new job opportunities when required to return to entirely on-site work. This trend highlights the critical importance of work-life balance and work flexibility policies for these demographics. As such, flexibility and balance are essential priorities that companies must incorporate into their workplace strategies. This study examines the moderating role of resilience in the relationship between work flexibility and work-life balance. The inclusion of resilience as a moderator seeks to address the inconsistent findings observed in prior studies concerning the impact of work flexibility on work-life balance. The research involved a purposive sample of 132 Generation Z and Millennial employees working in startup companies across Indonesia. Data analyzed using Smart Partial Least Square version 4.0. The results revealed that both work flexibility and resilience significantly influence work-life balance. However, resilience did not significantly moderate the relationship between work flexibility and work-life balance. These findings imply that while resilient individuals experience better work-life balance, resilience alone does not enhance the benefits of flexible work arrangements. For startup companies, offering flexibility remains a key strategy for supporting work-life balance. At the same time, organizations can further support their employees by fostering personal development and well-being through programs that build resilience. Combining both approaches may lead to a healthier, more motivated, and more productive workforce.